Comparison of Primary Mandibular First Molar Crown Dimensions with Stainless Steel Crowns in a Sample of Iranian Children - Mehdi Shahrabi; Alireza Heidari; Sanaz Kamareh (Tehran University of Medical Sciences, 2019)
Objectives: Attempts to retain primary teeth have led to introduction of materials and techniques for their preservation such as stainless steel crowns (SSCs). Due to variations in tooth anatomy among different populations, this study compared the buccolingual (BL) to mesiodistal (MD) ratio of primary mandibular first molars with that of SSCs in an Iranian population. Materials and Methods:  This cross sectional study was conducted on 96 primary mandibular first molars with intact cementoenamel junction, which had been extracted for severe caries. The MD and BL dimensions of the teeth and available maxillary and mandibular SSCs (3M) were measured. Two independent examiners measured the dimensions twice at two different time points using a digital caliper. Data were analyzed by one-sample t-test and McNemar's test via SPSS 21.0 software. Results: Significant differences were observed in both BL and MD dimensions between teeth and both maxillary and mandibular SSCs (P<0.001). According to McNemar's test, the dimensions of 65.6% of teeth matched those of mandibular SSCs while the dimensions of 38.5% matched those of maxillary crowns. Dimensions of 3.1% of the teeth did not match any of the crowns and in 7.4%, both maxillary and mandibular SSCs were appropriate. Conclusion: Comparing the variances of BL/MD ratio of teeth with SSCs revealed that the dimensions of two-thirds of the teeth matched those of mandibular SSCs, while the maxillary SSCs were appropriate for the remaining one-third. Significant differences were seen between the size of teeth and both maxillary and mandibular crowns.